Sexuelle Bildung ermöglichen: Sprachlosigkeit, Lust, Verletzbarkeit und Emanzipation als Herausforderungen pädagogischer Professionalisierung - Thuswald, Marion (2022)
How does teacher education prepare teachers for pedagogical challenges around sexuality in school? In her ethnographic research Marion Thuswald examines sex education courses in pre- and in-service teacher training. In her critical analysis of sex education pedagogies the author explores spaces for emancipatory sex education and develops practice relevant suggestions for schools and teacher education.